Polylactide-based nanocomposites with stereocomplex networks enhanced by GO-g-PDLA. (18th January 2017) - Zhang, Dongge; Lin, Yu; Wu, Guozhang
Abstract: Nanoparticle surfaces grafted with polymers similar to the matrix have been widely used to eliminate interface incompatibility and control the spatial organization of nanoparticles. However, the absence of specific interactions between the matrix and the graft limits the intrinsic versatility of nanoparticles, such as high mechanical strength, heat resistance, and excellent thermal/electrical conductivity. In this study, the specific interaction between poly(d -lactide)-grafted graphene oxide (GO- g -PDLA) and the poly(l -lactide) (PLLA) matrix was investigated via differential scanning calorimetry, dynamic mechanical analysis, electrical measurement, microscopy observation and in situ Fourier transform infrared spectroscopy (FTIR). In situ FTIR results reveal the formation process of stereocomplex crystallites (Sc) on the surface of grafted GO. Remarkable improvement of the crystallinity of stereocomplex nanocomposites was detected because of the heterogeneous nucleating effect of grafted GO. The GO-guided stereocomplex networks endow polylactide-based nanocomposites with significantly improved mechanical strength and electrical conductivity at low GO concentrations.